Spanish version of the scale of attitudes toward alcohol, alcoholism and alcoholics: content validation - Erika Gisseth León Ramírez; Divane de Vargas; Luz Patrícia Diaz Heredia; Alejandra Sepúlveda Corzo
ABSTACT Objective: to describe the process of translation and cultural adaptation of the scale of attitudes towards alcohol, alcoholism and alcoholics into the Spanish language. Methods: this was a methodological study, which followed the international guidelines for translation and adaptation of measurement scales. Results: During the process of translation and cultural adaptation of scale of attitudes towards alcohol, alcoholism and alcoholics to the Spanish language, the items were adjusted based on semantic, idiomatic and conceptual equivalence of the expressions contained in the scale of attitudes towards alcohol, alcoholism and alcoholics. Content validation indicated satisfactory validity indexes, with Intraclass Correlation Coefficient (ICC) (0.97), Content Validity Index (CVI) (0.92), and the Prevalence Adjusted Bias Adjusted Kappa (PABAK) (0.80). Conclusion: the scale of attitudes towards alcohol, alcoholism and alcoholics, adapted and translated into the Spanish language, presented content validity with satisfactory indexes, which affirmed that the instrument was adapted for the Colombian context. The next step will be evaluation of its psychometric properties in order to guarantee reliability for its use in Hispanic populations.